Visual thinking strategies : using art to deepen learning across school disciplines - Yenawine, Philip (Harvard Education Press, 2013)
"Visual Thinking Strategies (VTS), a teaching method that has been successfully implemented in schools and cultural institutions nationwide, provides for open-ended discussions of visual art that significantly increase students' critical thinking, language, and literacy skills. ... The book shows how VTS can be easily and effectively integrated into elementary classroom lessons in just ten hours a school year to create learner-centered environments where students at all levels are involved in rich, absorbing discussions."--Page 4 of cover.